Keragaman genetik cendawan entomopatogen Metarhizium anisopliae (Metsch.) berasal dari tanah pertanaman kelapa sawit berdasarkan penanda RAPD: Genetic diversity of the entomopathogenic Metarhizium anisopliae (Metsch.) from oil palm planting soil based on RAPD markers - Sirait, Desianty Dona Normalisa; Tobing, Maryani Cyccu; Safni, Irda (Jurnal Entomologi Indonesia, 2023)
Metarizhium anisopliae (Metsch.) is an entomopathogenic fungus that attacks Oryctes rhinoceros (Linnaeus). This fungus is one of the potential bioagents that is environmentally friendly. The purpose of this study was to isolate the fungus M. anisopliae from various oil palm plantation soil samples and to see its genetic diversity based on RAPD markers. The method used in this research is the morphological and the molecular identification of M. anisopliae (ITS), and genetic diversity testing using RAPD markers. Fifteen isolates of M. anisopliae isolated from 15 oil palm plantation sites in North Sumatra were examined for their molecular diversity. On the basis of morphological characteristics, all isolates were identified as M. anisopliae. The result of sequencing with the ITS primer showed that all isolates of M. anisopliae isolated from soil had a 85–99% homology of with M. anisopliae and M. brunneum reference strains from gen bank database National Center Biotechnology Information (NCBI). Eight RAPD primers generated 39 scorable bands which 38 (98,44%) of them were polymorphic. Clustering analysis was performed based on RAPD profiles using Neighbour-Joining Tree method that formed 3 groups.